STUDENTS’ PERCEPTION ON THE USE OF SOCIAL MEDIA IN LEARNING ENGLISH - Siswanti, Denti (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ibn Khaldun Bogor, 2026)
This study set out to investigate how students perceived utilizing social media platforms to improve English language skills. Transcripts of the interviews and supporting documentation were utilized to gather data for this qualitative case study research project. Four students from the Ganesha English lubuklinggau participated in the study . Considering the outcomes of the analysis that is descriptive , the majority of students thought that implementing social media to learn English was beneficial. Social media was thought to be beneficial for raising students' proficiency in the English language. They claimed the social media gives them access to English-language content sources where they can hone their language skills especially speaking, listening pronunciation and vocabularies . Additionally, social media provides range for English-language content, helping all of the students to select and access the content they want, whenever and wherever they want. The most popular accounts sites for learning English receptive skills, As an instance reading and listening, are Youtube and Instagram.